2002
DOI: 10.1089/15209150252924094
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Therapy with the Amylin Analogue Pramlintide Leads to a Combined Improvement in Glycemic and Weight Control in Insulin-Treated Subjects with Type 2 Diabetes

Abstract: The objective of this study was to assess the effect of mealtime amylin replacement with pramlintide on long-term glycemic and weight control in subjects with type 2 diabetes. This 52-week, randomized, placebo-controlled, multicenter, double-blind, dose-ranging study in 538 insulin-treated subjects with type 2 diabetes compared the efficacy and safety of 30-, 75-, or 150-microg doses of pramlintide, a synthetic analogue of the beta-cell hormone amylin, to placebo when injected subcutaneously three times daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
1
3

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(182 citation statements)
references
References 33 publications
3
170
1
3
Order By: Relevance
“…Several randomised, double-blind, placebo-controlled longterm trials on patients with type 2 diabetes have shown that the addition of pramlintide to pre-existing insulin regimens led to a further improvement in glycaemic control that was consistently accompanied by weight loss [34,35]. In recent pooled analyses of two long-term type 2 diabetes studies, 26 weeks of treatment with pramlintide (120 μg twice daily) led to a significant, placebo-corrected reduction in body weight that was progressive in nature, evident in subjects who did not report nausea, and most pronounced in subjects who were severely obese at baseline (averaging ∼3 kg in subjects with an entry BMI of >35 kg/m 2 ) [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several randomised, double-blind, placebo-controlled longterm trials on patients with type 2 diabetes have shown that the addition of pramlintide to pre-existing insulin regimens led to a further improvement in glycaemic control that was consistently accompanied by weight loss [34,35]. In recent pooled analyses of two long-term type 2 diabetes studies, 26 weeks of treatment with pramlintide (120 μg twice daily) led to a significant, placebo-corrected reduction in body weight that was progressive in nature, evident in subjects who did not report nausea, and most pronounced in subjects who were severely obese at baseline (averaging ∼3 kg in subjects with an entry BMI of >35 kg/m 2 ) [36].…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 120 μg was chosen because it has been widely studied in long-term trials [33][34][35], it has been shown to elicit a sustained reduction in body weight [33][34][35][36], and is intended for clinical use in insulin-treated subjects with type 2 diabetes. The preload meal consisted of 125 g of banana blended with 150 ml of low-fat (2%) milk and 150 ml of water (estimated energy content ∼189 kcal; 6 g protein, 36 g carbohydrate, 3 g fat), and was consumed within 3 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 A reduction in A1C of 0.5%-0.7% was achieved without increases in insulin use or significant increases in severe hypoglycemia 40 ( Figure 8). [46][47] It has also been shown that pramlintide decreases C-reactive protein and increases adiponectin, both of which are associated with inflammation and insulin resistance. The most common adverse event reported was mild to moderate nausea that dissipated early in treatment.…”
Section: The Impact Of Diabetes and Associated Cardiometabolic Risk Fmentioning
confidence: 99%
“…Pramlintide is administered 3 times a day with major meals in conjunction with insulin therapy to improve glycemic control. 47 Incretin-related therapies-GLP-1 is secreted in the small and large intestine in response to a meal along with glucose-dependent insulinotropic peptide (GIP). 48 Both regulate blood glucose by stimulating glucose-dependent insulin secretion, inhibiting gastric emptying, and inhibiting glucagon secretion.…”
Section: The Impact Of Diabetes and Associated Cardiometabolic Risk Fmentioning
confidence: 99%